Would that it were so simple: Dimensions of context diversity differentially relate to four implicit interethnic associations. Issue 6 (2nd November 2021) - Sadler, Melody; Somo, Angela; Devos, Thierry
ABSTRACT: Published studies point to heterogeneity in the relations between context diversity and implicit associations. To rule out methodological variations as an explanation, the relations between three dimensions of context diversity and four implicit associations were examined across 747 counties and 341 metropolitan areas, keeping constant as many factors as possible. Black people were evaluated more positively and were less associated with weapons in contexts with higher variety or higher integration combined with lower minority representation. Asian and Native Americans were more strongly associated with the American identity in contexts with higher minority representation and higher variety. These effects were largely consistent across context type, were seldom moderated by participant ethnicity, and held when controlling context-level education, median income, economic inequalities, proportion of U.S. citizens, and population density. The specificity of context diversity to implicit association relations is not attributable to methodological variations. Possible mechanisms underlying these effects are discussed.